If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 = 2(2x + -1) + 7 Reorder the terms: 5 + 5x = 2(2x + -1) + 7 Reorder the terms: 5 + 5x = 2(-1 + 2x) + 7 5 + 5x = (-1 * 2 + 2x * 2) + 7 5 + 5x = (-2 + 4x) + 7 Reorder the terms: 5 + 5x = -2 + 7 + 4x Combine like terms: -2 + 7 = 5 5 + 5x = 5 + 4x Add '-5' to each side of the equation. 5 + -5 + 5x = 5 + -5 + 4x Combine like terms: 5 + -5 = 0 0 + 5x = 5 + -5 + 4x 5x = 5 + -5 + 4x Combine like terms: 5 + -5 = 0 5x = 0 + 4x 5x = 4x Solving 5x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5x + -4x = 4x + -4x Combine like terms: 5x + -4x = 1x 1x = 4x + -4x Combine like terms: 4x + -4x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 8(x-6)=32 | | 0.6318*x^2*0.449x*5.832=0.223 | | 35=3x-6 | | 4y-6x= | | -3w+2+w=4 | | -3(x+2)-(8-5x)=x | | 5x^2+10x=-5 | | 73=(6k+42)+(6k+30) | | 7u=-5u+12 | | 1.2z=3z | | 4x+9y= | | -6(y+3)=-24 | | 2(x-15)=4(2+x) | | -1(-1-b)=19 | | (-2a)(a+3)= | | 9x+5=4(x+2)+5x | | 4x-13x-x=-30 | | -4n-2(5n+6)=27-n | | 4n+7-6=-32 | | n(n^2+n-1)=n^3 | | 3x+y=79 | | 120+(1.5p)=150+(1p) | | z-9=-2 | | 70-x-x-2x=90 | | W=.167zy | | -2+(-8x+9)=2(7x-4)+8 | | .6(x-8)=7.2 | | -2+5(3n-4)=5(-5n-2)+5 | | 11x-8+3x-5=10x-3+3 | | 1+11y=2+4(2y-7) | | -4x^6(10x+3x^2-7)= | | 30+2y=-3y |